Myth and Religion: The Cultural and Philosophical Significance of the Hero - Bravo, Nassim,; Charpenel, Eduardo,; Esparza, Gustavo, (New Research in the History of Western Philosophy ;, 2026)
This volume explores two fundamental questions. The first concerns the essence of the hero and the nature of heroic action. The second question has to do with the cultural role of the hero. This is an issue worth discussing, inasmuch as heroes often represent the worldview of a culture. The authors of this anthology contribute from their area of expertise to the analysis of these questions. The volume is divided into four thematic sections-classical studies, philosophical anthropology, philosophy of religion, and myth-criticism-each representing different philosophical approaches from which the figure of the hero can be explored.